Problems in the Education System and Their Solutions in Teaching History - Burliyev Toxir Norbayevich (Genius Journals, 2022)
This article talks about the problems in the education system and their solutions in teaching history today.
Keywords: Historical science; scientific and historical truth; teaching staff; education system